2022
DOI: 10.1021/acsestwater.2c00306
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater-Based Epidemiology for SARS-CoV-2 Biomarkers: Evaluation of Normalization Methods in Small and Large Communities in Southern Germany

Abstract: In the context of the COVID-19 pandemic, wastewater-based epidemiology (WBE) emerged as a useful tool to account for the prevalence of SARS-CoV-2 infections on a population scale. In this study, we analyzed wastewater samples from three large (>300,000 people served) and four small (<25,000 people served) communities throughout southern Germany from August to December 2021, capturing the fourth infection wave in Germany dominated by the Delta variant (B.1.617.2). As dilution can skew the SARS-CoV-2 biomarker c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Concentration of SARS-CoV-2 in wastewater is affected by the number of infected individuals and their respective viral shedding dynamics, but also by precipitation events, infiltration and inflow ( McCall et al, 2022 ), industrial flow contributions, and many other factors ( Soller et al, 2022 ; Wade et al, 2022 ; de Araújo et al, 2023 ; Mitranescu et al, 2022 ). Flow rates at wastewater sampling sites can be used to adjust for dilution, but flow data is not always available, especially for samples collected from manholes or small wastewater treatment facilities where no flow meter is present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration of SARS-CoV-2 in wastewater is affected by the number of infected individuals and their respective viral shedding dynamics, but also by precipitation events, infiltration and inflow ( McCall et al, 2022 ), industrial flow contributions, and many other factors ( Soller et al, 2022 ; Wade et al, 2022 ; de Araújo et al, 2023 ; Mitranescu et al, 2022 ). Flow rates at wastewater sampling sites can be used to adjust for dilution, but flow data is not always available, especially for samples collected from manholes or small wastewater treatment facilities where no flow meter is present.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has used correlation between wastewater and case data as a readout for the effectiveness of normalization methods, for determination of lead/lag times between datasets, and as a means to state the value of wastewater monitoring in general ( Greenwald et al, 2021 ; Ho et al, 2021 ; Mitranescu et al, 2022 ; Feng et al, 2021 ; Maal-Bared et al, 2023 ). However, statistical caveats of this analysis are often ignored – for example the fact that the correlation of two variables that measure the same phenomenon in a time series is inflated due to autocorrelation ( Hamed, 2009 ; Wolfe et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results from our study demonstrate that HF183 decays faster than PMMoV, meaning that PMMoV might be a better-normalizing marker than HF183 if the travel times are long. This is consistent with the findings of another recent publication, where it was reported that normalizing by the mean of two indicator biomarkers (PMMoV and crAssphage), produced better normalization results for COVID-19 cases than using either of the two virus biomarkers on their own …”
Section: Resultsmentioning
confidence: 99%
“…Other than PMMoV, Hsu et al (2022) found that Paraxanthine was a more reliable population biomarker than PMMoV. Mitranescu et al (2022) reported that the best normalization performance was achieved with a mixed fecal indicator calculated from both CrAssphage virus and PMMoV. It is crucial to note that these divergent conclusions were primarily attributed to the choice of matrix (solids versus liquid) ( D'Aoust et al, 2021 ; Wolfe et al, 2021 ) and variances in analytical methods ( Scott et al, 2021 ; Zhan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%